Towards Excellence in Asthma Management: Final Report of an Eight-Year Program Aimed at Reducing Care Gaps in Asthma Management in Quebec - Louis-Philippe Boulet; Eileen Dorval; Manon Labrecque; Michel Turgeon; Terrence Montague; Robert L Thivierge (Canadian Respiratory Journal)
BACKGROUND AND OBJECTIVES: Asthma care in Canada and around the world persistently falls short of optimal treatment. To optimize care, a systematic approach to identifying such shortfalls or ‘care gaps’, in which all stakeholders of the health care system (including patients) are involved, was proposed.